Affective Face Processing Modified by Different Tastes - Liang, Pei; Jiang, Jiayu; Chen, Jie; Wei, Liuqing (Frontiers in Psychology, 2021)
Emotional face search often takes place in our daily lives. How does the brain process the face search? Can taste modify such a process? This study employed two tastes (sweet and acid) to investigate the cross-modal interaction between taste and emotional face search. The behavior responses (reaction time and correct response ratios) and the event-related potential (ERP) were applied to analyze the interaction between taste and face processing. Behavior data showed that when detecting a negative target face with a positive face as a distractor, the participants perform the task faster with acid taste than with sweet taste. No interaction effect was observed with correct response ratio analysis. The early (P1, N170) and mid-stage (EPN) components have shown that sweet and acid taste modified the ERP components with the affective face search process in the ERP results. No interaction effect was observed in the late-stage (LPP) component. Our data have extended the understanding of the cross-modal mechanism and provided the electrophysiological evidence that the affective facial processing could be influenced by sweet and acid taste.